2013
DOI: 10.1097/fch.0b013e31828e671c
|View full text |Cite
|
Sign up to set email alerts
|

Leading Their Flocks to Health? Clergy Health and the Role of Clergy in Faith-Based Health Promotion Interventions

Abstract: Faith-based organizations are a frequent partner in health promotion due to their large and expansive reach across multiple demographics of the United States. These faith-based organizations are led by clergy members who have a strong influence over their institutions and who shape the physical and social environments of their institutions for health-related matters. The purpose of this review was to examine current issues associated with the health, behaviors, and well-being of clergy, highlight the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 58 publications
4
59
0
Order By: Relevance
“…The clergy are an important example of ‘gateway providers’ because they have a salient influence over their institutions and shape the physical and social environments for community health (Bopp et al . ). The clergy's knowledge and perceptions of mental health may determine the success of efforts to identify and address mental health needs in their congregation and the broader community (Taylor et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The clergy are an important example of ‘gateway providers’ because they have a salient influence over their institutions and shape the physical and social environments for community health (Bopp et al . ). The clergy's knowledge and perceptions of mental health may determine the success of efforts to identify and address mental health needs in their congregation and the broader community (Taylor et al .…”
Section: Introductionmentioning
confidence: 97%
“…The GPM emphasises the role of key community individuals who can facilitate the identification of mental health issues and provide a gateway to mental health services (Stiffman et al 2006, Ellis et al 2010. The clergy are an important example of 'gateway providers' because they have a salient influence over their institutions and shape the physical and social environments for community health (Bopp et al 2013). The clergy's knowledge and perceptions of mental health may determine the success of efforts to identify and address mental health needs in their congregation and the broader community (Taylor et al 2000, Yamada et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…According to one study, clergy reporting more comfort in providing health counseling and who had more positive perceptions of their own health were more likely to engage in health counseling in their FBOs [17]. Evidence also indicates that clergy with more positive health and behaviors are more likely to engage in health promotion in FBOs [18,19]. These findings are promising, but it is unknown if the health and behaviors of clergy influence whether they promote specific domains of health behavior such as PA.…”
Section: Introductionmentioning
confidence: 56%
“…Examination of other studies have revealed high rates of clergy burn-out and stress related issues (Bopp, Baruth, Peterson & Webb, 2013;Weaver, Flannelly, Larson, Stapleton, & Koenig, 2002), suggesting that the inclusions of policies for mental health, as mentioned by faith leaders in this study, are essential for improving and maintaining all aspects of health. The development of tailored policies to address clergy health, in partnership with health insurance providers, could result in healthier church environments, based on the link shown in other studies that have found that healthier faith leaders are more likely to have more health promotion programs in their own churches (Bopp & Fallon, 2011).…”
Section: Discussionmentioning
confidence: 99%